Hematological parameters and morphological characteristics of blood cells in turtle and tortoise species within captivity in Sri Lanka (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: This study was conducted to determine hematological reference ranges and morphological characteristics blood cells in healthy captive Sri Lankan fresh water turtle and tortoise species.Materials and Methods: Following turtle species, namely, Melanochelys trijuga parkeri (n = 06), M. trijuga thermalis (n = 06), and Lissemys punctata punctata (n = 06) and a tortoise species Geochelone elegans (n = 06) were evaluated. Blood smears were stained using Leishman–Gram staining protocol. The differential white blood cell counts and morphology were assessed using the standard protocols.Results: Both red blood cells and their nuclei were irregular in M. trijuga parkeri, whereas M. trijuga thermalis had oval-shaped and the nuclei were irregular in shape. L. punctata punctata and G. elegans had oval-shaped red blood cells and their nuclei were round in shape. In terms of differential counts, heterophils were the most abundant leukocyte type in all the species. Melanochelys trijuga parkeri had the highest heterophils value of 55% and the lowest value of 48.5% was recorded with G. elegans. Lymphocytes count was significantly high in G. elegans. Characteristic morphological features were observed in different leukocytes. In terms of thrombocytes, M. trijuga thermalis and L. punctata punctata had single platelets, whereas M. trijuga parkeri and G. elegans had platelets as clumps. Thrombocytes are ellipsoidal with centrally located dark-stained nuclei and their cytoplasm is clear.Conclusion: The findings in this study can be used as the reference values in the assessment of health of the above species and also will be useful in future hematological studies related to these species.J. Adv. Vet. Anim. Res., 6(3): 266-271, September 2019